Polynomials generating Hamming codes - Barashko, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A class of polynomials generating q-nary Hamming codes is studied. The criteria for a polynomial to belong to this class are established for the general case and for the case of prime polynomials. The conditions are determined under which reducible polynomials do not belong to the class of polynomials generating the q-nary Hamming codes.